1969
DOI: 10.1111/j.1432-1033.1969.tb00703.x
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Rotatory Dispersion Investigation of Fungal Laccase

Abstract: The optical rotatory dispersion curves for fungal laccase A and B have been determined in the wavelength region 200–750 nm. Both proteins show pronounced Cotton effects in the visible region. These are discussed in terms of possible chromophores (the so‐called Type 1 and Type 2 Cu2+ as well as the two diamagnetic copper ions). Various chemical treatments indicate that the anomalous dispersion is mainly associated with the blue, Type 1 Cu2+, which is thus coordinated in an asymmetric manner, but a small contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Discussion C.d. measurements showed that the Type 2 Cu(II) of lacquer-tree laccase does not significantly contribute to the optical activity of the protein in the 400-650nm region, in agreement with previous data concerning this and other multicopper blue proteins (Bossa et al, 1969;Falk & Reinhammar, 1972). On the other hand, it certainly contributes to the absorbance above 650nm; the A614/A750 ratio increased from about 4.6 in the native protein to about 6.5 in the partial apoprotein.…”
Section: Fluorescencesupporting
confidence: 90%
“…Discussion C.d. measurements showed that the Type 2 Cu(II) of lacquer-tree laccase does not significantly contribute to the optical activity of the protein in the 400-650nm region, in agreement with previous data concerning this and other multicopper blue proteins (Bossa et al, 1969;Falk & Reinhammar, 1972). On the other hand, it certainly contributes to the absorbance above 650nm; the A614/A750 ratio increased from about 4.6 in the native protein to about 6.5 in the partial apoprotein.…”
Section: Fluorescencesupporting
confidence: 90%
“…Experiments were carried out on the T-jump spectropolarimeter with the laccase-Mo(CN)f/3-system at the optically active 610 nm band [25] . No separate chemical relaxation could be resolved from that due to transmission change occurring upon reduction of the 610 nm band.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely the lowering of the dielectric constant of the environment, produced by the addition of sodium dodecyl sulfate in acidic solution (Konev, 1967) brings back the emission maximum to 310 nm (Figure 3). In this context it should be recalled that acidic pH {i.e., pH 1.5) leads to the disappearance (Tang and Coleman, 1967;Tang et al, 1968) of the multiple Cotton effects which are present in azurin and laccase at neutral pH (Tang and Coleman, 1967;Tang et al, 1968;Bossa et al, 1969) in the region of aromatic amino acids (270-300 nm). This indicates that dissymmetry and hydrophobic character are strictly associated in the tryptophan-containing part of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption spectra of most "blue" proteins show the characteristic ripples on the aromatic peak. Some of them have been found to have abnormal Cotton effects in the aromatic region (Tang and Coleman, 1967;Tang et al, 1968;Bossa et al, 1969).…”
Section: Discussionmentioning
confidence: 99%